2021
DOI: 10.1002/cam4.4184
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world comparison of docetaxel versus abiraterone acetate for metastatic hormone‐sensitive prostate cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A few clinical studies have compared the efficacy of ADT+docetaxel with that of ADT+abiraterone/prednisone in patients with mHSPC [ 7 8 9 10 ]. A network meta-analysis for mHSPC by Marchioni et al [ 7 ] showed that ADT+abiraterone/prednisone had a statistically significantly lower disease progression rate than ADT+docetaxel; however, no statistically significant difference in OS or adverse effect rate was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few clinical studies have compared the efficacy of ADT+docetaxel with that of ADT+abiraterone/prednisone in patients with mHSPC [ 7 8 9 10 ]. A network meta-analysis for mHSPC by Marchioni et al [ 7 ] showed that ADT+abiraterone/prednisone had a statistically significantly lower disease progression rate than ADT+docetaxel; however, no statistically significant difference in OS or adverse effect rate was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis and a few clinical studies have compared the efficacy of ADT+docetaxel with that of ADT+abiraterone/prednisone in patients with mHSPC [ 7 8 9 10 ]. However, only one multi-institutional study has been conducted, and all studies were not conducted in Korea [ 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis conducted by Wenzel et al., abiraterone treatment of mHSPC patients with high-volume disease resulted in a median OS of 50.1 months, which exceeded that of docetaxel (45.9 months) and ADT alone (34.0 months); no significant difference in the median OS was identified between docetaxel and ADT alone in the low-volume disease group ( 54 ). In a retrospective, multicenter study that compared the efficacy and safety of abiraterone and docetaxel in the treatment of mHSPC, the abiraterone+ADT group had a significantly longer PFS1, PFS2 (PFS1/PFS2, time from start of ADT to clinical, biochemical, or radiographic progression during first/second line or death from any cause) and OS as compared with the docetaxel+ADT group (23 vs 13 months; p < 0.001; 48 vs 33 months; p = 0.006; 80 vs 61 months; p = 0.040); according to a multivariate analysis of PFS1 (HR = 0.34, 95% CI 0.183–0.623; p = 0.001) and PFS2 (HR = 0.33, 95% CI 0.128–0.827, p = 0.018), abiraterone+ADT was significantly better than docetaxel+ADT, but both resulted in similar OS and toxic effects ( 56 ). The STAMPEDE clinical study demonstrated that the mean QoL score, over the period of 2 years, was +3.9 points higher in patients treated with abiraterone than in those treated with docetaxel, which fails to meet the predefined criterion for a clinically meaningful difference of >4.0 points; the mean QoL score was +5.7 points higher over 1 year, +7.0 points higher at 12 months, and +8.3 points higher at 24 months, suggesting that the patient-reported QoL was better in patients treated with abiraterone compared with those treated with docetaxel over a 2-year period ( 57 ).…”
Section: Comparison Of Combination Therapymentioning
confidence: 98%
“…Abiraterone (ABR) inhibits the biosynthesis of androgens and estrogens and is mainly used in combination with prednisone for the treatment of mCRPC patients who have previously received docetaxel-containing chemotherapy (4). With the in-depth study of abiraterone clinical trials in recent years, abiraterone was found to be useful in the treatment of newly diagnosed highrisk metastatic castration-sensitive prostate cancer (5)(6)(7). ABR, a steroidal antiandrogen, is insoluble in water, resulting in poor bioavailability (8).…”
Section: Introductionmentioning
confidence: 99%